A Generalized Reversal Model for the Solvatochromism of Merocyanines - Caroli-Rezende, M (John Wiley and Sons Ltd, 2016)
The solvatochromic behaviour of merocyanines can be interpreted and predicted by consideration of their molecular structure with the aid of a model that regards all kinds of solvatochromism as particular cases of a generalized reverse behaviour. This generalized reversal model is shown to be consistent with the cyanine-limit model, another independent approach that relates the merocyanine structure with its solvatochromic behaviour. Both models are validated by experimental data from the literature of 21 merocyanines of variable molecular structure. Copyright © 2016 John Wiley & Sons, Ltd. Copyright © 2016 John Wiley & Sons, Ltd.